Human Metapneumovirus: Mechanisms and Molecular Targets Used by the Virus to Avoid the Immune System - Soto, Jorge A.; Gálvez, Nicolás M. S.; Benavente, Felipe M.; Pizarro-Ortega, Magdalena S.; Lay, Margarita K.; Riedel, Claudia; Bueno, Susan M.; Gonzalez, Pablo A.; Kalergis, Alexis M. (Frontiers in Immunology, 2018)
Human Metapneumovirus (hMPV) is a respiratory virus, which was discovered in the year 2001. Since then, it has been described as one of the main etiological agent that causes acute lower respiratory tract infections (ALRTIs), which is characterized by symptoms such as bronchiolitis, wheezing and coughing. Susceptible population to hMPV infection include newborn, children, the elderly and immunocompromised individuals. This viral agent is a negative-stranded RNA enveloped virus, that belongs to the Pneumoviridae family and Metapneumovirus genus. Different reports state that several cases of respiratory illness before 2001 could be related to hMPV infection. Despite the similarities of hMPV with several other viruses, such as human respiratory syncytial virus (hRSV) or influenza virus, it is still unclear the mechanism used by hMPV to avoid the host immune system. In fact, the evidence indicates that a poor innate immune response is generated by hMPV, affecting the adaptive immune response. It has been reported low cytokine secretion that could induce poor polarization and activation of T cells and/or the promotion of an anergic state in these cells. The evidences support that this virus interferes with several pattern recognition receptors (PRRs) and cell signaling pathways triggered by the interferon (IFN)-associated genes. However, the mechanisms used by hMPV seem to be different than hRSV, which uses NS1 and NS2 proteins to inhibit these pathways. There are evidences that suggest that glycoproteins like G and SH could play roles in the mechanism of infection. To the other hand, secretion of thymic stromal lymphopoietin (TSLP) cytokine during hMPV infection and it could dramatically affect the antiviral host immune response. The aim of this review, it is to examine and to discuss those findings reported in the literature directed to understand the mechanisms that underlie the poor immune response elicited by hMPV infection. Importantly, these mechanisms will be discussed and compared with other respiratory viruses that also induced low respiratory infection.